2023
DOI: 10.3390/jpm13060998
|View full text |Cite
|
Sign up to set email alerts
|

Serum and Bronchoalveolar Lavage Fluid Levels of Cytokines in Patients with Lung Cancer and Chronic Lung Disease: A Prospective Comparative Study

Abstract: The role of chronic inflammation in the initiation and progression of carcinogenesis has been well-established in previous studies, particularly in the stages of malignant conversion, invasion, and metastasis. This study aimed to explore the potential correlation between the levels of cytokines in serum and bronchoalveolar lavage fluid (BALF) by comparing their levels between patients with lung cancer and those with benign lung diseases. The study measured the concentration of IFN-γ, TNF-α, IL-1β, IL-2, IL-4, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 45 publications
(68 reference statements)
0
2
0
Order By: Relevance
“…Metabolic syndrome, hypertension, and T2DM have been shown to be associated with NAFLD, and insulin resistance is a major contributor to metabolic syndrome and enhances the development of NAFLD ( 42 - 44 ). Chronic inflammation has been found to be involved in the development of lung cancer ( 45 ). Therefore, these factors may also be involved in the associations between NAFLD and pulmonary nodules in patients with intestinal polyps, however, future studies are needed to elucidate the specific mechanisms underlying these associations.…”
Section: Discussionmentioning
confidence: 99%
“…Metabolic syndrome, hypertension, and T2DM have been shown to be associated with NAFLD, and insulin resistance is a major contributor to metabolic syndrome and enhances the development of NAFLD ( 42 - 44 ). Chronic inflammation has been found to be involved in the development of lung cancer ( 45 ). Therefore, these factors may also be involved in the associations between NAFLD and pulmonary nodules in patients with intestinal polyps, however, future studies are needed to elucidate the specific mechanisms underlying these associations.…”
Section: Discussionmentioning
confidence: 99%
“…The geographical location of individuals, especially their proximity to main roads and industrial areas, has been observed to correlate with the severity and frequency of COPD exacerbations [20][21][22]. Traffic-related air pollution, characterized by high levels of particulate matter, has been increasingly linked to respiratory morbidity and mortality [23][24][25]. Consequently, investigating the impact of these environmental factors, combined with particle size considerations, is vital in constructing a nuanced understanding of exacerbation patterns among COPD patients, particularly within the GOLD 3 and GOLD 4 categories.…”
Section: Introductionmentioning
confidence: 99%